2017
DOI: 10.1016/j.joen.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Glide Path Enlargement of Mandibular Molar Canals by Using K-files, the ProGlider File, and G-Files: A Comparative Study of the Preparation Times

Abstract: Glide path preparation times with the rotary instrument groups were significantly faster than with stainless steel manual K-files.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
6

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 24 publications
2
32
0
6
Order By: Relevance
“…We observed statistically significant differences regarding the same and found that the PathFile system was faster. The time taken to perform the glide path using different systems has been previously evaluated and compared (4,20,21,23). In concordance with our findings, the results of a recent research conducted by Paleker et al (20) show that the rotary files analyzed in their study (G-File and ProGlider) are faster than the manual files used to create a glide path.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We observed statistically significant differences regarding the same and found that the PathFile system was faster. The time taken to perform the glide path using different systems has been previously evaluated and compared (4,20,21,23). In concordance with our findings, the results of a recent research conducted by Paleker et al (20) show that the rotary files analyzed in their study (G-File and ProGlider) are faster than the manual files used to create a glide path.…”
Section: Discussionsupporting
confidence: 89%
“…The time taken to perform the glide path using different systems has been previously evaluated and compared (4,20,21,23). In concordance with our findings, the results of a recent research conducted by Paleker et al (20) show that the rotary files analyzed in their study (G-File and ProGlider) are faster than the manual files used to create a glide path. Another recent study (21) compared the glide path enlargement times of the ProGlider, PathFile, X-Plorer Canal Navigation Ni-Ti files, and stainless steel K-files.…”
Section: Discussionsupporting
confidence: 89%
“…Several instruments and techniques have been suggested for the preparation of glide paths, including hand preparation with stainless steel K‐files, the combination of reciprocating handpiece and stainless steel K‐files or the use of a less tapered motor‐driven nickel–titanium (NiTi) rotary instrument (Gambarini , Nakagawa et al . , Paleker & van der Vyver ). The use of NiTi rotary instruments has been associated with a less time‐consuming and safer glide path preparation that respects the original canal anatomy (Nakagawa et al .…”
Section: Introductionmentioning
confidence: 99%
“…The use of NiTi rotary instruments has been associated with a less time‐consuming and safer glide path preparation that respects the original canal anatomy (Nakagawa et al . , Paleker & van der Vyver ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation